2020
DOI: 10.1080/21655979.2020.1827892
|View full text |Cite
|
Sign up to set email alerts
|

New findings in the roles of Cyclin-dependent Kinase inhibitors 2B Antisense RNA 1 ( CDKN2B-AS1 ) rs1333049 G/C and rs4977574 A/G variants on the risk to coronary heart disease

Abstract: The relationship between Cyclin-Dependent Kinase Inhibitors 2B Antisense RNA 1 (CDKN2B-AS1) variants rs1333049 G/C and rs4977574 A/G and the risk of coronary heart disease is unclear. We conducted an update analysis incorporating odds ratios and 95% confidence intervals to assess the correlation. Furthermore, we used in silico analysis to investigate the genes and proteins that interact with CDKN2B. Fifty case-control studies with a sample size of 35,915 cases and 48,873 controls were involved. We revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In the current meta‐analysis, a subgroup analysis stratified by ethnicity was performed. Yuan et al also performed a meta‐analysis on rs4977574 polymorphism and CHD in 2020 and obtained similar results 51 . However, in their meta‐analysis, individual studies deviating from HWE were included.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the current meta‐analysis, a subgroup analysis stratified by ethnicity was performed. Yuan et al also performed a meta‐analysis on rs4977574 polymorphism and CHD in 2020 and obtained similar results 51 . However, in their meta‐analysis, individual studies deviating from HWE were included.…”
Section: Discussionmentioning
confidence: 81%
“…Yuan et al also performed a meta‐analysis on rs4977574 polymorphism and CHD in 2020 and obtained similar results. 51 However, in their meta‐analysis, individual studies deviating from HWE were included. Although they divided the participating subjects into three subgroups, namely West Asian, East Asian, and Caucasian, the included individual studies were not complete yet.…”
Section: Discussionmentioning
confidence: 99%
“…Obtained results confirmed the association of the G-allele with an increased risk of CAD occurrence. In the last few years, the results of three independent meta-analyses performed by Chinese researchers have also been published [24][25][26]. The significant link between ANRIL gene rs4977574 polymorphism and the development of CAD and myocardial infarction was reported.…”
Section: Development Of Various Atherosclerosis Complications Have Be...mentioning
confidence: 99%
“…We have shown that the frequency of the rs4977574-G allele in the control group was 0.438, while in the common case group: 0.516. According to the 1000 Genomes project, the average frequency of G-alleles in the global population is 0.395; in Europeans: 0.492; in the population of both Americas: 0.416; in Central Asia: 0.531; in South Asia: 0.484; and in the African populations: 0.141 [26]. More detailed data from the European countries have shown that the G-allele frequency in Sweden population is 0.448 [20] and in the Finnish It is known that the polymorphic locus rs4977574 is located in the 16 th intron of the ANRIL gene (103785 th position).…”
Section: Development Of Various Atherosclerosis Complications Have Be...mentioning
confidence: 99%
“…The development of the social economy and changes in people’s lifestyles have led to high incidence and mortality rates for coronary heart disease [ 1 ]. Its mortality rate exceeds that of tumors and other diseases, and ranks first as a cause of death [ 2 ].…”
Section: Introductionmentioning
confidence: 99%